(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article discusses the importance of early diagnosis of motor disorders in prematurely born children. The main patterns of harmonious child development, the features of monitoring premature children, risk factors, and the role of a physical therapist in a multidisciplinary team when working with such patients are highlighted. Studies and scientific works on early diagnosis and the features of the work of a physical therapist when interacting with a family where a child was born prematurely are analyzed. The motor characteristics of a child, namely its regularity, are an essential early diagnostic criterion. Due to several genetic and environmental factors, development can be disrupted, one of the reasons being premature birth. It has been established that early detection of motor function disorders is crucial for the subsequent treatment and rehabilitation process since, in the first year of life, the number of synapses increases by 50%, which is a matter of using neuroplasticity. Observations of prematurely born children suggest that, in general, the formation of a child’s psychomotor functions corresponds to the stages of development of children born at term, which is within the normal range, but the timing of appearance is subject to other laws and is associated with the level of morphofunctional immaturity, gestational age, and the degree of perinatal damage. Premature infants are more likely to exhibit neurobehavioral changes at term, with abnormal reflexes, greater hypotonia or hypertonia, poorer quality of movement, poorer orientation, greater excitability, and more stress. The earlier certain disorders are diagnosed, the more effective the therapy and the better the outcome. Early initiation of work with a physical therapist is fundamental. We must use time as efficiently as possible to eliminate diagnosed disorders, restore full health, and prevent disability.